2000
DOI: 10.3189/172756500781832611
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene climate conditions in the north Chilean Andes drawn from a climate–glacier model

Abstract: A climate–glacier model was used to reconstruct Late-glacial climate conditions from two case-study glaciers at 18° and 22° S in the arid (sub)tropical western Andes of northern Chile. The model uses (i) the geometry of the Late-glacial maximum glaciation, (ii) modern diurnal and annual cycles, amplitudes and lapse rates of the climate, (iii) empirical–statistical sublimation, melt and accumulation models developed for this area, and (iv) dynamic ice flow through two known cross-sections for steady-state condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 22 publications
4
94
0
1
Order By: Relevance
“…The prominent moraines of the glacier modeled by Kull and Grosjean (2000) have not, however, been previously dated. Here, we present 8 new cosmogenic 36 Cl exposure ages.…”
Section: El Tatio Morainesmentioning
confidence: 99%
See 3 more Smart Citations
“…The prominent moraines of the glacier modeled by Kull and Grosjean (2000) have not, however, been previously dated. Here, we present 8 new cosmogenic 36 Cl exposure ages.…”
Section: El Tatio Morainesmentioning
confidence: 99%
“…Much of the drift surrounding this valley, on the other hand, is thin and exhibits patterning (as described above in Section 3.4) and poor development of lateral moraines, all of which may indicate thin, cold-based ice. Glacial-climate modeling by Kull and Grosjean (2000) based on the prominent moraines indicated that an extra 1 m of precipitation could be necessary to generate this glacier in conjunction with a 3.5ºC temperature depression as was characteristic of the Late Glacial. The model indicated, based on modern precipitation patterns, that most of this moisture must have come from the east during the austral summer.…”
Section: El Tatio Morainesmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect is compensated for in the model by using a mean correction term of AT = -2øC fbr the calculation of temperatures over snow/ice surf;aces compared to gravel surfiaces [Sicart et al, 1998;Kull, 1999;Kull and Grosjean, 2000]. In addition, long-term means of lapse rates fi'om test sites with homogeneous surf;aces were used [l/uille, 1996;Kull, 1999].…”
Section: Meteorological Datamentioning
confidence: 99%